Restoration of the anterior crowded teeth as a stage of comprehensive rehabilitation of the patient - Голинка, Ольга Павловна (Actual Dentistry, 2019)
Summary. The restoration of hard dental tissues defects accompanied by a change in color and shape is a common manipulation in clinical practice. The restoration f the anterior group of teeth in case of their crowding and combined with dental caries as a part of complex rehabilitation has its own special aspects. A clinical case of restoration with the use of Ukrainian-made restoration materials «Jen-Radiance» and «Jen-Favorite» (Jendental-Ukraine LLC) is described. Key words: teeth, crowding, treatment, restoration, composite.